PENGARUH PENERAPAN GOOD AGRICULTURE PRACTICE DAN STRATEGI ADAPTASI PERUBAHAN IKLIM PADA PRODUKSI BAWANG MERAH DALAM UPAYA MENINGKATKAN KESEJAHTERAAN PETANI (Studi Kasus Di Desa Mojorejo Kecamatan Kedungadem Kabupaten Bojonegoro) - Fauzi Adi Wibowo; Agustina Shinta Hartati W; Riyanti Isaskar (Jurnal Penelitian Pendidikan IPA, 2025)
As with other horticultural crops, shallot production is influenced by the local climate (season). This research aims to find out how Good Agriculture Practice and climate change adaptation strategies are implemented in shallot production in Mojorejo village, Kedungadem District, Bojonegoro Regency, and to find out how the application of Good Agriculture Practice and climate change adaptation strategies in shallot production affects farmers' welfare. The analysis used in this research is descriptive statistical analysis and Partial Least Squares SEM (PLS-SEM). Sampling was carried out using the Slovin formula with the proportionate sampling method, namely 51 respondents. The results of the research show that the influence of good agricultural practices and climate change adaptation strategies on red onion production on welfare has a positive and positive impact of 0.47. In the good agricultural practice variable, the most dominant regulation is social analysis, 0.89, in the strategic variable adapting to non-water climate change, the most dominant is 0.91 in plant management. The most dominant regional welfare variable is social security management at 0.88. With the implementation of good agricultural practices and strategies for adapting to changes in climate, the health and level of leadership of agricultural families increases.